انمـاط ما وراء الانفعـال لدى معلـمي رياضيات المرحلـة الابتدائيـة (Journal of the College of Basic Education, 2023)
The current research aimed to identify (patterns beyond emotion among primary school mathematics teachers) and to achieve this, the researcher chose a random sample of (60) teachers from governmental primary schools affiliated to the Baghdad / Karkh district, and the data was processed by statistical means using the statistical bag ( (Spss) in the procedures and data analysis of the current research. The researcher concluded that: Elementary school mathematics teachers enjoy a positive style in dealing with students' emotions represented by the emotion education (training) style.